Innovations and investments for transforming India’s rice economy: Submergence tolerant rice varieties in rainfed lowlands of North-Eastern Uttar Pradesh - RAVINDRA, RAVINDRA; SINGH, ALKA; PERUMAL, ANBUKKANI (The Indian Journal of Agricultural Sciences, 2020)
The present study provides a brief overview of India’s R&D program and orientation of the public and private research portfolio and investments in reference to the rice research. The farm level and aggregate potential economic benefits from the adoption of improved submergence tolerant rice varieties (Swarna Sub 1, Samba Masuri Sub 1) in the rainfed lowland region of India were estimated based on a field survey conducted in rainfed lowlands of the northeastern region of Uttar Pradesh state. At farm-level, the submergence tolerant varieties had not only 39% higher yield advantage and 63% higher net returns as compared to other popularly grown varieties in the region, but also showed lower yield risk under the prevailing conditions. At the aggregate level, potential benefits from the adoption of these stress-tolerant varieties were also estimated. Farmers’ perception showed that Swarna Sub 1 and Samba Masuri Sub 1 rice varieties are preferred mainly because of their better tolerance to the submergence conditions prevailing in the area during the rainy season. Sarjoo-52 is an old variety but still preferred due to its taste, yield and resistance to pests and diseases. The results amply indicate that farmers’ perception of crop varietal attributes influences largely their choice of varieties at the farm level.